Reading Fluency in Spanish Patients with Alzheimer’s Disease - del Carmen Pèrez-Sánchez, María; González-Nosti, María; Cuetos, Fernando; Martínez, Carmen; Álvarez-Cañizo, Marta (Current Alzheimer Research, 2021)
Background: Reading fluency is essential for our functioning in the literate society in which we live. Reading expressiveness or prosody, along with speed and accuracy, are considered key aspects of fluent reading. Prosodic patterns may vary, not being the same in children learning to read as in adulthood. But little is known about the prosodic characteristics and reading fluency of people with neurodegenerative diseases that causes language impairment and reading difficulties, such as Alzheimer’s disease (AD). Objective: The aim of this work was to study reading fluency in AD, considering reading speed, accuracy and reading prosody. Methods: The participants were 20 healthy elderly Spanish adults, and 20 AD patients, aged 64-88 years. An experimental text was designed, that included declarative, exclamatory, and interrogative sentences, words with different stresses and low-frequency words. The reading of the participants was recorded and analyzed using Praat software. Results: The AD group showed significantly longer reading duration, both at the syllable level and at the word and sentence level. These patients also committed more pauses between words, which were also longer, and more reading errors. The control group showed a variation of the syllabic F0 in the three types of sentences, while these variations only appeared in declarative ones in the AD group. Conclusion: The pauses, along with the slight pitch variations and the longer reading times and errors committed, compromise the reading fluency of people with AD. Assessment of this reading feature could be interesting as a possible diagnostic marker for the disease.
Keywords: Alzheimer' s disease